1998
DOI: 10.1046/j.1365-2222.1998.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the tryptase release test and the cellular allergen stimulation test (CAST) in mite sensitive patients

Abstract: The partial discrepancies observed could be interpreted as a consequence of conditions that were technically not optimal. False-positive results may be due to the action of some non-specific cytotoxic agent, false-negative results may be due to hyporesponsive basophils or the low number of cells participating in the reaction and finally, in the case of TRT, to G4 monoclonal antibody to tryptase employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…produces specific IgE antibodies, while the in vitro reactivity of human basophils may be considered a reflection of clinical status (Lichtenstein and McGlashan 1986). The performance of the CAST in human diagnostic application is comparable to that obtained in the horse; for allergy to mites, Rossi et al (1998) reported a sensitivity and specificity of the CAST with Dermatophagoides farinae of 71% and 87%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…produces specific IgE antibodies, while the in vitro reactivity of human basophils may be considered a reflection of clinical status (Lichtenstein and McGlashan 1986). The performance of the CAST in human diagnostic application is comparable to that obtained in the horse; for allergy to mites, Rossi et al (1998) reported a sensitivity and specificity of the CAST with Dermatophagoides farinae of 71% and 87%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Using a cut‐off of 5% as positive the overall sensitivity was 51.4%, with 10% as the cut‐off this dropped to 22.8%; the specificities were 63% and 79.5%, respectively. Receiver operating characteristic curves should be employed in order to determine the appropriate cut‐off points [8].…”
Section: Non‐commercial Assays For Determination Of Basophil Activationmentioning
confidence: 99%
“…Similar findings were made by Rossi et al . [8] in a series of 247 mite sensitve patients. The assay appeared to offer good diagnostic performance for D pteronyssinus and D farinae with positive predictive values quoted of 88% and 91%, respectively.…”
Section: Commercial Assays For Determination Of Basophil Activationmentioning
confidence: 99%
“…Tests based on CysLT release after allergen challenge may be interesting but further studies are required (1291)(1292)(1293). More data are needed to fully appreciate the value of these tests.…”
Section: In Vitro Testsmentioning
confidence: 99%